Pengaruh Fasilitas Kantor, Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai Bappeda Kabupaten Batang Hari - Etty Siswati; Niki Kosasi; Evi Fauzani; Rezha Syafutra (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to see how much influence office facilities, work motivation, and work discipline have on employee performance BAPPEDA Kabupaten Batang Hari. This research includes quantitative descriptive research. The sample of this study was 72 respondents. Based on the results of the research and discussion, some of the main conclusions of the study can be explained as follows: From the results of the research that the author has done, the results of the partial test (t test). The value of tcount for (X1) office facilities is 3,515 and the value of ttable is 1,66629 because the value of tcount is greater than the value of ttable, it can be concluded that office facilities have a significant effect on employee performance Kantor BAPPEDA Kabupaten Batang Hari. For (X2) work motivation is -0.349 and the value of ttable is 1.66629, because the value of tcount is smaller than the value of ttable, it can be concluded that work motivation has no effect on employee performance BAPPEDA Kabupaten Batanag Hari , And for (X3) work discipline is -1.731 and the value of ttable is 1.66629 because the value of tcount is greater than the value of ttable, it can be concluded that work discipline has no significant effect (negative bias) on employee performance BAPEDDA Kabupaten Batang Hari. Simultaneous test results (test together) Fcount 4.147 is greater than Ftable 2.34. It means that together the variables of Office Facilities, Work Motivation, Work Discipline have an effect on Employee PerformanceKantor BAPPEDA Kabupaten Batang hari